FUCNTIONS OF CUSTOMARY LAW IN MANAGING WATER MANAGEMENT WITHIN FARMERS’ ORGANIZATION: Case of Subak Kedua, Denpasar City, Bali Province, Indonesia - Putu Dyatmikawati (STKIP Singkawang, 2017)
Irrigation water management in Bali province, Indonesia has been well known due to the existence of traditional irrigation system, called subak. Subak is not only an institution in agriculture, but also as a part of Bali’s local wisdom. The philosophy of the subak system is Tri Hita Karana (three causes of happiness) which a basis for subak to manage irrigation and farming activities. The objective of this study is to describe the subak as organization and functions of customary law in sustaining the activities on farming and irrigation in subak system. The results of study point out that subak as an organization employs traditional management to members, particularly in irrigation and rice farming activities. In order to manage these activities, subak has established customary law based on the traditions happened in the community where subak is located and based on the Tri Hita Karana. Thus subak’s customary law is specific location in nature. Therefore, the main contents of customary law concerning the parhyangan (relationship between farmers and God), pawongan (relationship among farmers) and and palemahan (relationship between farmers and environment). Applying Tri Hita Karana, subak ensures to achieve the harmony among the members and management board and make sustainable irrigation system.